Penerapan Sistem Informasi Presensi Pengunjung Perpustakaan Berbasis RFID di SMA Negeri 1 Pamekasan - Sholeh Rachmatullah; Nirwana Haidar Hari (Gapenas Publisher, 2022)
SMA Negeri 1 Pamekasan is one of the favorite schools in Pamekasan Regency which was the International Standard School Pioneer (RSBI) in 2009-2014. However, library activities are still carried out completely manually. Visiting library members are not properly recorded, many problems occur during the circulation process, difficulties in searching for books, book collections are not completely recorded and without labeling, they are only stored in excel form. This will hinder the process of reporting and presenting data in statistical form. The solution offered by the Community Service (PKM) team with the 2019 RISTEKDIKTI funding source is to switch to a digital library based on Radio Frequency Identification (RFID) technology to facilitate visitor recapitulation, book collection searches, circulation processes and bibliography. The digital library is designed with a client server network topology and uses a modified SLIM application so that it can be integrated with the use of RFID cards. The RFID card functions as a library membership card as well as a student card, Teacher and Tu ID card. All library members have used their identity cards to carry out transactions at the library including attendance by sticking the card on the smartcard reader, borrowing and returning reading books